Research handbook on the law of virtual and augmented reality - Barfield, Woodrow, 1950-; Blitz, Marc Jonathan; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
The proliferation of virtual and augmented reality technologies into society raise significant questions for judges, legal institutions, and policy makers. For example, when should activities that occur in virtual worlds, or virtual images that are projected into real space (that is, augmented reality), count as protected First Amendment 'speech'? When should they instead count as a nuisance or trespass? Under what circumstances would the copying of virtual images infringe intellectual property laws, or the output of intelligent virtual avatars be patentable inventions or works of authorship eligible for copyright? And when should a person (or computer) face legal consequences for allegedly harmful virtual acts? The Research Handbook on the Law of Virtual and Augmented Reality addresses these questions and others, drawing upon free speech doctrine, criminal law, the law of data protection and privacy, and of jurisdiction, as well as upon potential legal rights for increasingly intelligent virtual avatars in VR worlds. The Research Handbook offers a comprehensive look at challenges to various legal doctrines raised by the emergence - and increasing use - of virtual and augmented reality worlds, and at how existing law in the USA, Europe, and other jurisdictions might apply to these emerging technologies, or evolve to address them. It also considers what legal questions about virtual and augmented reality are likely to be important, not just for judges and legal scholars, but also for the established businesses and start-ups that wish to make use of, and help shape, these important new technologies. This comprehensive Research Handbook will be an invaluable reference to those looking to keep pace with the dynamic field of virtual and augmented reality, including students and researchers studying intellectual property law as well as legal practitioners, computer scientists, engineers, game designers, and business owners.
Section I. Introduction to the law of virtual and augmented reality -- 1. The law of virtual reality and increasingly smart virtual avatars / Woodrow Barfield and Alexander Williams -- 2. Starting up in virtual reality: examining virtual reality as a space for innovation / Crystal Nwaneri -- 3. Virtual rule of law / Michael Risch -- 4. Mixed reality: how the laws of virtual worlds govern everyday life / Josh A.T. Fairfield -- Part II Intellectual property law -- 5. Virtual copyright / Michael Risch and Jack Russo -- 6. Trademark and the right of publicity in augmented reality / Brian D. Wassom, Amber M. Underhill and Andrew L. Rossow -- 7. Virtual trade dress / Jack Russo -- Part III -- Issues of constitutional and criminal law -- 8. First amendment, video games and virtual / Marc Jonathan Blitz -- 9. Virtual reality, haptics, and first amendment protection for sexual sensation / Brooke Lewis ---10. Augmented and virtual reality, freedom of expression, and the personalization of public space / Marc Jonathan Blitz -- 11. Beyond unauthorized access: laws of virtual reality hacking / Gilad Yadin -- 12. The law and ethics of virtual sexual assault / John Danaher -- 13. Criminal liability for intellectual property offenses of artificially intelligent entities in virtual and augmented reality environments / Gabriel Hallevy -- Part IV Applying the law to different applications of virtual and augmented reality -- 14. Advertising legal issues in virtual and augmented reality / S. J. Blodgett- Ford, Woodrow Barfield and Alexander Williams -- 15. Data privacy legal issues in virtual and augmented reality advertising / S. J. Blodgett- Ford and Mirjam Supponen -- 16. Reordering the chaos of the virtual arena: harmonizing law and framing collective bargaining for avatar actors and digital athletes / Jon Garon -- Part V Contract, property law, and jurisdiction ---17. Property rights in virtual and augmented reality: second life versus Pokémon Go / Hannah YeeFen LIM -- 18. Freedom of contract in augmented reality / Scott R. Peppet -- 19. Law and property in virtual worlds / Wian Erlank -- 20. Legal jurisdiction and the deterritorialization of social life / Paul Schiff Berman -- Index.
Obsahuje bibliografie, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: virtuální realita; rozšířená realita; virtual reality; augmented reality; e-knihy online; e-books online